Choosing Wisely—Finding the Gap: Assessment of Transfusion Practices. (21st September 2018) - Van Buren, Nancy; Tomlinson, Kara; Kvasnicka, John
Abstract: Objectives: The Choosing Wisely (CW) initiative published a list of recommendations in collaboration with specialty societies to assist with improving medical practice. One of the recommendations in transfusion medicine focused on avoiding liberal red blood cell (RBC) transfusions, which was based on evidence supporting restrictive transfusion strategies. As part of a quality initiative within our hospital system, it was utilized to measure current transfusion practices. Methods: A quality project template was developed utilizing CW guidelines in various areas of practice in 2015. A cross-sectional survey of RBC transfusions was conducted. The objective was to identify opportunities for improvement through a process to identify gaps. The CW recommendation of not transfusing more units of blood than absolutely necessary was selected. Chart review was undertaken when the "other" category was selected in the transfusion order set when the indication was outside of the accepted parameters established by the Transfusion Committee following recommended guidelines. This data were compiled after review by task force members and presented to the hospital system's Accountable Care Organization (ACO). An action plan was created to address gaps in practice through collaboration with the quality council and the task force with results reported to the ACO quality committee. Results: During the 3-month period in 2015, 2, 209 transfusions were evaluated based on indications documented by the ordering physician through computerized physician order entry (CPOE). The reason for transfusion was documented as "other" in 134 (6.1%). Following chart review of this category, appropriate reasons were not identified for transfusion in 3.8%, which represented 0.002% of total transfusions. Conclusion: Patient blood management (PBM) is highly relevant to laboratory professionals and other specialties. This study demonstrates that educational efforts across disciplines to tighten transfusion guidelines during a PBM initiative were successful. CW recommendations can be used to assess quality of practice in medicine.